FACTORS THAT DETERMINE DIVIDEND POLICY ON BANKING IN THE INDONESIA STOCK EXCHANGE - Mega Febriani; Farah Margaretha (Universitas Trisakti, 2018)
The problem of this research was to test and analyze empirically the influence to financial characteristics, ownership structure and board structure that have significant effects on dividend decisions. The objective of this research was banking firm that listed in Indonesian Stock Exchange for period 2010-2017. The methodology of this research was applies purposive sampling. The data obtained in this the secondary data was taken from Indonesian Stock Exchange. This research was panel least square model and processed using software eviews 9. Total number of samples is 27 companies. The purpose of this test is to prove the effect of the independent variables on the dependent variable.The result of this research shows that the financial characteristics, significant effected dividend decisions, meanwhile profitability, likuidity, free cash flow. Growth opportunity, age, size, leverage and asset tangibility does not effects the dividend decisions. Ownership structure significant effected dividend decisions, meanwhile institusional ownership and goverment ownership. And board structure significant effected dividend decisions, meanwhile independen director. The Managerial Implications from this research are how the company manages the capital sources from free cash flow and likuidity, how to make the company can be efficient in running the company and make earning.